Factors Influencing Responsible Behavior and Destination Choice of Visitors: A Case Study of Chiang Khan Community, Loei Province - Untong, Akarapong; Guntawongwan, Kansinee (Journal of Research Methodology, 2024)
This study aims to investigate the causal relationship between factors influencing Thai visitors’ responsible behavior and their choice of Chiang Khan as a tourism destination. The model consists of six latent variables measured from 20 observational variables. The sample comprised 298 Thai visitors who visited Chiang Khan, located in Loei province. Questionnaires were utilized as the research tool, while structural equation modeling was applied to analyze the data. The results indicate that focusing on social participation and increasing awareness of responsible tourism management are two key factors influencing visitors’ responsible behavior and their choice of Chiang Khan as a tourist destination. Therefore, to encourage responsible behavior among visitors and promote Chiang Khan as a tourism destination, relevant sectors should develop and disseminate information on responsible tourism stewardship and management through various channels, such as video clips, online and social media platforms, influencers, etc., to effectively communicate with visitors and interested parties.